Dysbiotic Lesional Microbiome With Filaggrin Missense Variants Associate With Atopic Dermatitis in India - Nath, Shankha (Front Cell Infect Microbiol, 2020)
Background: Atopic Dermatitis (AD) has been associated with the loss of function (LoF) mutations in Filaggrin (FLG) gene and increase in relative abundance of specific microbes in the lesional skin, predominantly in Caucasians. Our study aims to determine, in Indian AD patients, (a) the prevalence of FLG LoF and missense mutations, and (b) the nature and extent of dysbiosis and altered microbial pathways with and without mutations in FLG. AD patients (n = 34) and healthy controls (n = 54) were recruited from India in this study and shotgun sequencing was carried out in a subset of samples with adequate microbiome DNA concentration. Host DNA from the same subset of samples was subjected to FLG coding region sequencing and host-microbiome association was estimated. Results: The prevalence of FLG LoFs that are associated with AD globally were significantly lesser in our cases and controls (8.6%, 0%) than those reported in Europeans (27%, 2.6%). Staphylococcus aureus was present only on AD skin [abundance in Pediatric AD: 32.86%; Adult AD: 22.17%], but not on healthy skin on which Staphylococcus hominis (Adult controls: 16.43%, Adult AD: 0.20%; p = 0.002), Cutibacterium acnes (Adult controls:10.84%, Adult AD: 0.90%; p = 0.02), and Malassezia globosa (Adult controls: 8.89%, Adult AD: 0.005%; p = 0.001) were significantly more abundant. Microbial pathways mostly associated with skin barrier permeability, ammonia production and inflammation (Arginine and Proline metabolism, Histidine Metabolism and Staphylococcus aureus infection) were significantly enriched on AD skin metagenome. These pathways are also reported to impair antimicrobial peptide activity. Among AD patients with missense single nucleotide polymorphisms harboring “potentially damaging” alleles in FLG gene, damaging allele dosage was significantly (p < 0.02) positively correlated with relative abundance of phylum_Proteobacteria up to order_Pseudomonadales and negatively correlated with phylum_Firmicutes up to species_Staphylococcus aureus. Conclusion: Our study has provided evidence that host DNA profile is significantly associated with microbiome composition in the development of AD. Species and strain level analysis showed that the microbial pathways enriched in AD cases were mostly found in MRSA strains. These evidences can be harnessed to control AD by modulating the microbiome using a personalized strategy. Our findings on the association of FLG genotypes with the microbiome dysbiosis may pave the way for a personalized strategy to provide a more effective control of AD.